Communication skills who's afraid of grammar? - Nathan, Leslie Ann; Cotton, Eve; The Center for Humanities (Mt. Kisco, NY : The Center for Humanities)
Defines standard English, introduces basic concepts of English structures, provides instruction in the formation of simple sentences, and tells how to combine sentences.
Title from title screen.
DVD format.
Keywords: English language -- Grammar -- 1950-; Grammar; Communication